2018
DOI: 10.1590/0103-8478cr20180044
|View full text |Cite
|
Sign up to set email alerts
|

Yield analysis of Physalis ixocarpa Brot. ex Hornem varieties under greenhouse and field conditions

Abstract: Physalis ixocarpa (husk tomato) is traditionally cultivated in Mexico, and nowadays the yield is low. In this study, four cultivars of husk tomato were evaluated, under greenhouse and field conditions. It was carried out a split-plot experimental design in a 4x2 factorial arrangement. The large plot was the growth conditions and the small plot was the variety. The microclimate, soil and yield variables were recorded. In the field, the Integrated Photosynthetic Active Radiation (IPAR) was higher 12mol m-2 d-1 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
2
2
0
2
Order By: Relevance
“…The values of vertical diameter were higher when tomatillos were grown without soil and plant covers. Similar values were reported by Ramos-López et al [5]-3.84 cm to 4.90 cm, depending on husk tomato cultivar and cultivation method. Singh et al [38] reported a diameter of 2.27-3.73 cm for Physalis ixocarpa Brot.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The values of vertical diameter were higher when tomatillos were grown without soil and plant covers. Similar values were reported by Ramos-López et al [5]-3.84 cm to 4.90 cm, depending on husk tomato cultivar and cultivation method. Singh et al [38] reported a diameter of 2.27-3.73 cm for Physalis ixocarpa Brot.…”
Section: Discussionsupporting
confidence: 90%
“…'Rio Grande Verde' were grown in mulch under non-woven PP fabric covers. Similar results were reported by Ramos-López et al [5], who found that plant covers had a significant effect on the weight of husk tomato fruit which ranged from 26.10 g in cv. 'Rendidora' to 52.29 g in cv.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…En este sentido, el manejo de un invernadero agrícola con respecto al sistema de temporal presenta la ventaja de controlar el suministro de agua e insumos según el estado fenológico del cultivo. Además, limita la entrada de plagas y modifica factores ambientales, tales como la temperatura, radiación solar, humedad relativa, disponibilidad de CO2, luminosidad y velocidad del viento (Peña-Lomelí et al, 2014;Ramos-López et al, 2018;Tanny, 2012). Ramos-López et al (2017) evaluaron el rendimiento de tomate de cáscara en invernadero, revestido con distintas cubiertas plásticas, obteniendo la mayor producción (3.23 kg planta -1 ) cuando fue cubierto con polietileno transparente.…”
Section: Issn Online 2007-9621unclassified